Localized superoxide release by neutrophils can be provoked by a cytosolic calcium 'cloud'. - Davies, E V (1991)
We have used single-cell ratio imaging of Fura-2 loaded neutrophils to visualize release of cytosolic Ca2+ from an intracellular store in order to determine the location of this store and the relationship of release from it to oxidase activation. In the presence of extracellular Ca2+, N-formyl-L-methionyl-L-leucyl-L-phenylalanine (FMLP) produced an increase in free Ca2+ throughout the cytosol. In its absence, however, stimulation induced in 38% of neutrophils a highly localized increase in cytosolic free Ca2+, located between the nuclear lobes and the plasma membrane, at a region of cytosol which stained positively with 3,3'-dihexyloxacarbocyanine iodide [DiOC6(3)]. Calcium release from the store was transient, without oscillation and occurred after delays of up to 120 seconds. Addition of Ca2+ ionophore also released Ca2+ from this, and other stores, within the cell, up to three foci being detected in some cells. Localized oxidase activation occurred at the plasma membrane when the calcium concentration ([Ca2+]) of the 'cloud' exceeded 250 nM. Surprisingly, localized activation occurred at the plasma membrane at a site separate from but near to a region of high Ca2+. It was concluded that release of Ca2+ from a single receptor-releasable, Ca2+ store in neutrophils was insufficient to trigger oxidase activation throughout the cell, but could provide a localized activation of the oxidase.